Variabilidad genética de doncella Pseudoplatystoma punctifer (Castelnau, 1855) en siete poblaciones naturales de la amazonía peruana - Alvarado Reátegui, Jhon Gregory (2018)
This study aimed to determine the genetic variability of 203 specimens of doncella Pseudoplatystoma punctifer from seven natural populations of the Peruvian Amazon through the analysis of 8 microsatellite loci. The results show a high genetic variability in the species (113 alleles found, with an average of 13.14 alleles per locus). The correspondence factor analysis showed the existence of genetic differentiation between some populations of this species, in addition, the results of the fixation index (FST), Number of migrants per generation (Nm) and genetic distance showed that the populations of Madre de Dios and Nanay present the greatest genetic differences between them (FST = 0.115, Nm = 1.93; D = 0.349) and also with the rest of the populations (Madre de Dios: FST varies from = 0.039 to 0.057; Nm = 4.16 to 6.24; D = 0.135 to 0.174; Nanay: FST varies from = 0.060 to 0.080, Nm = 2. 88 to 3.95; D = 0.165 to 0.222). It was also observed that the populations of the Marañon and Ucayali rivers do not show genetic structuring between them (FST = 0.00; Nm = infinity; D = 0.003). The results of the genetic structuring analysis corroborated these results, showing three evolutionary units among the seven populations analyzed (K = 3). The differences found among these fish populations could be related to isolation by geographic distance in the case of Madre de Dios or isolation by the difference in the type of water in the case of Nanay.